PID dual speed motor controller for mobile robot application - Mohd Syahmi, Sharif (2009)
Robot becomes widely used in industrial due to their characteristics. Robot able to work in 24 hours continuously without feeling tired unlike human that confine to certain time. The cost to setup the robot nowadays becomes more affordable and their long term prospect is bright judging from their capacity to perform. But in reality, there is no robot able to function perfectly and still making error. A better controller needed here, to allow the robot performs efficiently and make less error. This project try to implement a PID controller on mobile robot to see whether the robot perform efficiently. This mobile robot has encoder for each two wheel to give feedback pulse width modulation (PWM) at PIC controller to do PID algorithm. When PID have implemented, the robot will be able to moving along the track straight and smoothly.